Independent impact assessment report: Participatory Rangeland Management (PRM) in Kenya and Tanzania - Waweru, T.; Maina, J.; Liheta, B.; Apunda, E. (African Research and Economic Development Consultants Limited, 2021)
This report comprises findings from an independent impact assessment of the Piloting Participatory Rangeland Management project in Kenya and Tanzania. The study was conducted in November and December 2021 by African Re search and Economic Development Consultants (AFREDEC), contracted by ILRI Livestock CRP (CGIAR Research Program). The main objective was to determine the impacts of participatory rangeland management (PRM) on rangelands, environment, good governance and management processes, security of rights to land and resources, livestock production, gender issues, women’s empowerment and other social equity aspects and on policy influence. The study identified key lessons learnt and best practices and opportunities for scaling up. The assessment applied a mixed-method approach comprising quantitative data collected using household surveys and qualitative data collected using key informant interviews and focus group discussions. In total, 2,000 household representatives were interviewed through the survey, with almost 150 focus group discussion participants and more than 40 key informants.